Tuberculosis Monitoring Encouragement Adherence Drive (TMEAD): Toward improving the adherence of the patients with drug-sensitive tuberculosis in Nashik, Maharashtra - Saha, Somen; Saxena, Deepak; Raval, Devang; Halkarni, Nishad; Doshi, Rahul; Joshi, Madhav; Sridharan, Mridhula; Sathwara, Jignasa; Yasobant, Sandul; Shah, Harsh; Quazi, Zahiruddin Syed; Rajsekar, Kavitha; et al. (Frontiers in Public Health, 2022)
Introduction Adherence to tuberculosis (TB) medication is one of the critical challenges to tuberculosis elimination in India. Digital adherence technologies (DAT) have the potential to facilitate medication adherence and monitor it remotely. Tuberculosis Monitoring Encouragement Adherence Drive (TMEAD) is one such DAT piloted in Nasik, Maharashtra, from April 2020 to December 2021. The study aims to assess the adherence and cost-effectiveness of TMEAD compared to the standard of care among patients with drug-sensitive tuberculosis (DSTB) residing in the urban areas of Nasik, Maharashtra, India. Methods A quasi-experimental study was conducted among new cases of TB as per the National TB Elimination Programme (NTEP) residing in the urban geography of Nasik. The intervention and control arms were purposively selected from non-contaminating TB units (TUs). A total of 400 DSTB patients (200 in the intervention group and 200 in the control group) were enrolled. After enrolment, patients in the intervention arm were provided with the TMEAD device and followed for 24 weeks to assess treatment outcomes. Adherence was measured as those patients who have completed 80% of prescribed doses, as reported during patient follow-up, and further validated by analyzing the trace of rifampicin in urine among 20% of patients from both arms. A budget impact analysis was done to assess the impact of the TMEAD program on the overall state health budget. Results Out of 400 enrolled DSTB patients, 261 patients completed treatment, 108 patients were on treatment, 15 patients died, and 16 patients were defaulters over the study period. The study reported overall treatment adherence of 94% among those who completed treatment. Patient reports indicated high levels of treatment adherence in the intervention group (99%) as compared to the control group (90%). Adherence assessed through analyzing trace of rifampicin in the urine sample for the intervention arm was 84% compared to the control arm (80%). Per beneficiary (discounted) cost for TMEAD was Indian rupees (INR) 6,573 (USD 83). The incremental cost-effectiveness ratio of the intervention is INR 11,599 (USD 146), which shows that the intervention is highly cost-effective. Conclusion This study revealed that patient-reported treatment adherence was high in TMEAD when compared to standard therapy of care for DSTB patients and the intervention is cost-effective. TMEAD could complement the national strategy to end TB by improving adherence to the treatment regimen in India.